The immune checkpoint molecule B7-H4 regulates β-cell mass and insulin secretion by modulating cholesterol metabolism through Stat5 signalling - Fangzhen Xia; Ziteng Zhang; Zhen Qian; Xiaoyu Fang; Junxue Wang; Yan Wang; Guoting Sun; Yuefeng Yu; Ninjian Wang; Junke Zhen; Yan Liu; Yingli Lu (Molecular Metabolism)
Objective: B7-H4 (B7S1, B7x, VTCN1) is an important immune checkpoint molecule that maintains immune homeostasis and is also expressed in pancreatic β cells. The polymorphism of B7-H4 influences the prevalence of Type 2 diabetes (T2D), suggesting a potential role of B7-H4 in the physiological function of pancreatic β cells and the pathogenesis of T2D. Methods: β-cell-specific B7-H4 knockout mice (B7-H4 cKO mice) and their wild-type littermates were used to investigate the in vivo effects of B7-H4 on pancreatic β-cell morphology and function. AAV2/8-ins2-B7H4 and a control virus were infused via the pancreatic intraduct into high-fat diet (HFD)-treated mice to elucidate the therapeutic effect of B7-H4. RNA sequencing was conducted on primary islets. A Luminex assay was used to quantify cytokine changes in B7-H4 cKO mice. Electron microscopy imaging was used to observe insulin secretory vesicles in pancreatic β cells. Results: Lesion of B7-H4 in β cells results in glucose intolerance due to reduced β-cell mass and deficient insulin secretion, whereas overexpression of B7-H4 in β cells ameliorates glucose intolerance in HFD-fed mice. Mechanistically, B7-H4 deficiency activates signal transducer and activator of transcription 5 (Stat5) signalling, which inhibits the expression of apolipoprotein F (Apof), leading to reduced cholesterol efflux and accumulated cholesterol in β cells, thereby impairing insulin processing and secretion. Overexpression of Apof in β cells or intraperitoneal injection of a Stat5 inhibitor reverses the metabolic phenotype and insulin secretion deficiency in B7-H4 cKO mice. Conclusion: Our study demonstrated that B7-H4 plays an important role in regulating β-cell mass and insulin secretion, which may shed new light on the development of novel strategies for T2D treatment.